The Position of Mediation in the Settlement of Sharia Economic Disputes in Indonesia - Harahap, Sarah Khairani; Mujib, Abdul (Islamic Economic Law Programs, Faculty of Sharia and Law, UIN Sunan Ampel Surabaya, 2025)
Abstract: This study examines the strategic role of mediation in resolving Sharia economic disputes within Indonesia’s Religious Courts, where mediation is normatively recognized as a fast, cost-effective, and Sharia-aligned mechanism, yet remains underutilized in pre-litigation contexts. Using a normative-empirical method, the research analyzes primary legal instruments—such as Law No. 30/1999, PERMA No. 1/2016, PERMA No. 14/2016, and Law No. 3/2006 alongside conceptual frameworks of islah, while empirical data were obtained from the Supreme Court’s 2024 annual report, case statistics from Religious Courts in Yogyakarta, literature reviews, and interviews with certified non-judge mediators. The findings show a significant increase in mediation success rates in litigated Sharia economic cases during 2023–2024, particularly in PA Bantul, demonstrating the growing effectiveness of mediation and the strong philosophical foundation provided by Islamic principles of justice, reconciliation, and maslahah. However, the study also identifies persistent obstacles to the wider adoption of pre-litigation mediation, including the absence of mandatory regulatory requirements, limited contractual mediation clauses, low legal literacy, and misconceptions regarding the enforceability of out-of-court agreements. These results highlight the need for regulatory reform, broader integration of mediation clauses in Sharia economic contracts, and increasing public understanding to optimize mediation as a mechanism for resolving major disputes outside the court that is sharia-compliant, efficient, modern, and restorative justice-oriented. Keywords: Mediation, Sharia Economics, Dispute Resolution. Abstrak: Penelitian ini mengkaji peran strategis mediasi dalam penyelesaian sengketa ekonomi syariah di lingkungan Peradilan Agama di Indonesia, di mana mediasi secara normatif diakui sebagai mekanisme penyelesaian yang cepat, hemat biaya, dan selaras dengan prinsip syariah, namun masih belum dimanfaatkan secara optimal pada tahap pra-litigasi. Dengan menggunakan metode normatif-empiris, penelitian ini menganalisis instrumen hukum primer seperti UU No. 30/1999, PERMA No. 1/2016, PERMA No. 14/2016, dan UU No. 3/2006 serta kerangka konseptual tentang islah, sementara data empiris diperoleh dari Laporan Tahunan Mahkamah Agung 2024, statistik perkara di Pengadilan Agama wilayah Yogyakarta, studi literatur, dan wawancara dengan mediator non-hakim bersertifikat. Temuan penelitian menunjukkan adanya peningkatan signifikan tingkat keberhasilan mediasi litigasi pada perkara ekonomi syariah selama 2023–2024, terutama di PA Bantul, yang menggambarkan meningkatnya efektivitas mediasi dan kuatnya landasan filosofis yang diberikan oleh prinsip keadilan, rekonsiliasi, dan maslahah dalam Islam. Namun demikian, penelitian ini juga mengidentifikasi hambatan yang menghalangi penerapan mediasi pra-litigasi secara lebih luas, termasuk tidak adanya kewajiban regulatif, minimnya pencantuman klausul mediasi dalam kontrak ekonomi syariah, rendahnya literasi hukum, serta kesalahpahaman mengenai kekuatan eksekutorial kesepakatan mediasi di luar pengadilan. Hasil penelitian menegaskan pentingnya reformasi regulasi, integrasi klausul mediasi dalam kontrak ekonomi syariah, serta peningkatan pemahaman publik untuk mengoptimalkan mediasi sebagai mekanisme penyelesaian sengketa utama diluar pengadilan yang sesuai syariah, efisien, modern, dan berorientasi pada keadilan restoratif. Kata Kunci: Mediasi, Ekonomi Syariah, Penyelesaian Sengketa.